2016
DOI: 10.1111/jcmm.12786
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IL‐8‐Src signalling axis by 17β‐estradiol inhibits human mesenchymal stem cells‐mediated gastric cancer invasion

Abstract: Epidemiologic data show the incidence of gastric cancer in men is twofold higher than in women worldwide. Oestrogen is reported to have the capacity against gastric cancer development. Endogenous oestrogen reduces gastric cancer incidence in women. Cancer patients treated with oestrogens have a lower subsequent risk of gastric cancer. Accumulating studies report that bone marrow mesenchymal stem cells (BMMSCs) might contribute to the progression of gastric cancer through paracrine effect of soluble factors. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…A previous study found that seed cells contributed less to the final repair of bone tissue, compared to host-derived cells [12]. Here, we showed that BMSCs on tissue engineering bone release a large amount of IL-8, while some studies have shown that IL-8 is a chemotaxis to MSCs in vitro [33][34][35][36]. In this study, transwell experiments were done to confirm that IL-8 has a chemotactic effect on BMSCs.…”
Section: Discussionmentioning
confidence: 59%
“…A previous study found that seed cells contributed less to the final repair of bone tissue, compared to host-derived cells [12]. Here, we showed that BMSCs on tissue engineering bone release a large amount of IL-8, while some studies have shown that IL-8 is a chemotaxis to MSCs in vitro [33][34][35][36]. In this study, transwell experiments were done to confirm that IL-8 has a chemotactic effect on BMSCs.…”
Section: Discussionmentioning
confidence: 59%
“…Only a few studies have examined its anti-inflammatory effects on cells such as microglial cells (6,7) and macrophages (3). Furthermore, IL-8, a member of the CXC chemokine family, is involved in inflammatory responses, leukocyte chemotaxis and cancer development (18,19). The high expression of IL-8 is markedly associated with the proliferation, invasion and migration of gastric epithelial cells (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Signals initiated by VEGF or IL-8 are transduced into cells through the activation of Src [29, 30]. A previous study shows that Src is an upstream of Vav2 in controlling Rac1 activation [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Src plays a critical role in regulating Rho GTPases such as Rac1, and one of the major functions of Src is to modulate the actin cytoskeleton that controls cell migration. A recent study reported that IL-8 up-regulated motility activity through Src signaling in human gastric cancer cells [29]. Src signaling has also been shown to be involved in VEGF-induced angiogenesis [30].…”
Section: Introductionmentioning
confidence: 99%